Treatment method of aluminum electrolysis solid waste

By water-impregnating and acid-impregnating aluminum electrolytic solid waste, it destroys its embedded structure, exposes lithium and carbon elements, and then through flotation and decomposition treatment, it can efficiently recover valuable elements such as lithium and ice crystals, solve the problems of large consumption of medicines and in-depth recycling of resources in the prior art, and achieve resource utilization and environmental protection effects.

CN119662984AActive Publication Date: 2025-03-21CINF ENG CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411840095.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-13
Publication Date
2025-03-21
Estimated Expiration
2044-12-13

AI Technical Summary

Technical Problem

The prior art consumes a large amount of agent when dealing with aluminum electrolytic solid waste, and fails to effectively realize the deep recycling of valuable elements such as lithium and ice crystals, resulting in waste of resources and environmental pollution.

Method used

By mixing aluminum electrolytic solid waste powder with water, water impregnation and acid impregnation treatment, the embedded structure in the acid impregnation slag is destroyed, the carbon and lithium elements in the raw materials are exposed and dissociated, and then the recycling and resource utilization of valuable elements such as lithium and ice crystals is achieved through flotation and decomposition treatment.

Benefits of technology

It has achieved efficient recycling of valuable elements such as lithium and ice crystals in aluminum electrolytic solid waste, reduced the consumption of drugs, improved resource utilization, and simple processing process, low cost, and significant environmental protection effect.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention relates to a treatment method of aluminum electrolysis solid waste. The treatment method comprises the following steps: providing aluminum electrolysis solid waste powder; wherein the aluminum electrolysis solid waste powder comprises overhaul slag and waste slag, the overhaul slag comprises one or more of waste refractory materials and waste cathodes, the waste slag comprises one or two of waste carbon slag and waste aluminum electrolyte, and the mass ratio of the overhaul slag to the waste slag is (6-8): (1-4); uniformly mixing the aluminum electrolyte solid waste powder with water according to the solid-liquid mass ratio of 1: (3-5), reacting at the temperature of 80-95 DEG C, and performing solid-liquid separation to obtain leached residues and leached liquid; and after acid leaching is conducted on the leaching residues, solid-liquid separation is conducted, and acid leaching residues and acid leaching liquid rich in lithium are obtained. According to the treatment method, various aluminum electrolysis solid wastes such as aluminum electrolysis waste refractory materials and waste residues can be treated at the same time. The treatment method provided by the invention can realize full-quantitative recovery of carbon, lithium, cryolite and other substances in the aluminum electrolysis solid waste, and has good economic benefits.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a method for treating aluminum electrolysis solid waste, and in particular to a method for resource treatment of aluminum electrolysis solid waste, belonging to the technical field of harmless resource treatment of solid waste and hazardous waste. Background Art

[0002] At present, the Hall-Heroult molten salt electrolysis method is the main process for aluminum smelting production. During the production of electrolytic aluminum, due to the penetration and corrosion of the molten high-temperature electrolyte, the lining structure of the electrolytic cell is deformed and broken, and the aluminum liquid and electrolyte in the cell leak into the bottom of the electrolytic cell from the cracks, making the electrolytic cell unable to be used normally. Therefore, on average, the aluminum electrolytic cell needs to be overhauled every 5 to 8 years, generating a large amount of waste electrolyte, waste cathode, waste carbon slag and waste refractory materials. According to statistics, for every ton of electrolytic aluminum produced, 10 to 15 kg of waste cathode, 6 to 16 kg of waste carbon slag, 14 kg of waste electrolyte and 10 to 15 kg of waste refractory materials will be generated, so it is necessary to further process these aluminum electrolytic solid wastes.

[0003] Aluminum electrolysis solid waste often contains toxic substances such as cyanide and fluoride. In the past, they were often directly stored in the open air or buried on site. This not only occupied land resources, but also dissolved toxic substances and released harmful gases due to long-term exposure to rainy seasons or humid environments, polluting the surrounding environment and water bodies.

[0004] The "heart" of new energy vehicles is lithium batteries, and the core raw material for manufacturing lithium batteries is "lithium carbonate". With the rapid development of new energy vehicles, the demand for lithium carbonate has increased sharply, and the demand has increased every year. Aluminum electrolysis solid waste contains 0.43-2% metallic lithium, and the grade is close to that of lithium mica ore. In addition, the waste cathode also contains more than 55% graphitized carbon, the waste carbon slag contains more than 22% carbon, the waste electrolyte contains more than 60% cryolite, and the waste refractory material also contains 0.45-1.5% lithium. Therefore, aluminum electrolysis solid waste has huge comprehensive recycling value.

[0005] Based on the above background, on the basis of harmless treatment, further green and high-value utilization of aluminum electrolysis solid waste is carried out to extract valuable elements such as lithium carbonate, graphite and cryolite, which becomes a win-win move that turns waste into treasure and benefits the country and the people.

[0006] The research on overhaul slag (waste tank lining, often including waste refractory materials and waste cathode) abroad began in 1946, and many treatment methods including pyrolysis and hydrolysis were studied. Pyrolysis is generally divided into three steps, first the combustion of carbonaceous materials, then the oxidation and decomposition of cyanide, and finally the conversion of fluoride, which is mainly based on harmless treatment and will not produce secondary pollution. Represented by Alcoa, Rio Tinto (Cormac Aluminum, Alcan), etc., they have successfully developed harmless treatment technology for waste tank lining with their own characteristics and independent intellectual property rights and implemented it industrially, and built and put into production harmless treatment plants of waste tank lining of different sizes. Since 1996, the US Environmental Protection Agency has banned the open-air storage and soil burial of waste tank linings, requiring aluminum smelters to carry out harmless treatment. Up to now, the waste tank linings discharged by aluminum smelters in Europe and the United States have basically been harmlessly treated. The research on overhaul slag in China started late. At present, the main treatment methods for overhaul slag include heat treatment, high temperature hydrolysis, flotation, acid leaching, etc. Some researchers have used limestone as a reactant and fly ash as an additive to treat the waste tank lining pyrolysis process (also known as rotary kiln roasting method). The soluble fluoride conversion rate of the waste tank lining reached more than 98%, and the cyanide removal rate reached more than 99.5%. The average soluble F in the harmless slag after treatment was 1.347 million tons. - Content 39.7mg / L, CN - The content is 0.053mg / L, which is lower than the standard requirement of "Hazardous Waste Identification Standard Leaching Toxicity Identification" (GB 5085.3-2007). Wet treatment methods such as acid leaching and flotation can partially achieve the harmlessness and resource utilization of overhaul slag. Some scholars crushed the waste lining of the electrolytic cell into pulp, added cyanide removal agent hypochlorite, and CN - Oxidized into non-toxic N2 and CO2, and then added with defluoridation agent quicklime and hydrochloric acid to make F - It generates water-insoluble CaF2, thus achieving the purpose of fluorine removal.

[0007] In general, the current industrial treatment of overhaul slag is mainly based on landfill after harmless treatment, and the deep recovery of valuable resources therein has not been achieved.

[0008] Waste carbon slag and waste cathode are mainly composed of carbon and some cryolite, and have certain recycling value. At present, the technology that can achieve industrial resource recovery of carbon slag / waste cathode is mainly wet process. The wet process utilizes the physical and chemical properties of different components in the carbon slag, and recovers and recycles the fluorine-containing electrolyte and carbon components in the carbon slag / waste cathode through crushing-ball milling-flotation treatment. The wet flotation process basically realizes the primary resource utilization of carbon slag, but the quality of by-product carbon powder and electrolyte does not meet the requirements of industrial products and needs further treatment. Many researchers have also conducted extensive research on the pyrometallurgical recovery process of carbon slag. The pyrometallurgical process generally uses a chemical reactor, which integrates oxidative combustion, catalytic conversion, gasification and impurity removal, tempering and homogenization, and flue gas treatment. The heating method uses electricity or gas, etc. It mainly uses high-temperature combustion of carbon in carbon slag / waste cathode, and the product is regenerated cryolite. The technical disadvantages of the pyrometallurgical process are the life of the combustion chamber and the treatment of fluorine-containing gases. The process technology has high energy consumption and cannot recover the carbon of the raw materials, resulting in great waste. The advantage is that the purity and quality of the regenerated cryolite produced are good. This process is used in China for the purification of electrolytes in wet flotation of carbon slag / waste cathodes, and there are very few projects for industrial use in the treatment of carbon slag / waste cathodes in electrolytic aluminum plants.

[0009] Due to the pressure of processing costs and increasingly stringent environmental protection requirements, electrolytic aluminum companies have little motivation to recycle carbon slag as a resource, and many of them simply adopt the method of landfill after harmless treatment.

[0010] With the long-term operation of aluminum electrolytic cells, impurities and additives in the raw materials will be enriched in the electrolyte, causing the properties of the electrolyte to change, resulting in low cell temperature, poor alumina dissolution ability, and more precipitation at the bottom of the cell. In order to ensure the normal and stable operation of the electrolytic cell, the current conventional practice is to regularly extract a portion of high-impurity electrolyte from the produced electrolytic cell and add some new electrolyte for replacement, so as to ensure that the total amount of impurities is within the range required by the process. The replaced electrolyte contains a high amount of valuable components and can generally be used for the initial start-up of the electrolytic cell of a newly built aluminum electrolytic plant after simple treatment. However, as the domestic aluminum electrolytic production capacity has basically stabilized in recent years, it is no longer possible to rely on the initial start-up tank of aluminum electrolytic plant to digest this part of the electrolyte. The replaced waste electrolyte cannot be directly returned to the electrolytic cell for use, but can only be stored in large quantities, which not only causes a waste of resources, but also creates new environmental hazards. At present, for waste electrolytes, research and development have been conducted on resource recovery methods that use a combination of wet or pyrometallurgical and wet methods, but their raw material limitations are high and the consumption of reagents is high. Summary of the invention

[0011] In view of the deficiencies in the prior art, an object of the present invention is to provide a method for treating aluminum electrolysis solid waste with lower reagent consumption.

[0012] In order to solve the above technical problems, the technical solution of the present invention is as follows:

[0013] A method for treating aluminum electrolysis solid waste comprises the following steps:

[0014] S1. Provide aluminum electrolysis solid waste powder;

[0015] The aluminum electrolysis solid waste powder includes overhaul slag and waste slag, the overhaul slag includes one or more of waste refractory materials and waste cathodes, the waste slag includes one or two of waste carbon slag and waste aluminum electrolyte, and the mass ratio of the overhaul slag to the waste slag is 6-8:1-4;

[0016] S2, mixing the aluminum electrolyte solid waste powder and water in a solid-liquid mass ratio of 1:3-5, reacting at 80-95° C., separating the solid and the liquid to obtain leaching residue and leaching liquid;

[0017] S3, after acid leaching the leached residue, solid-liquid separation is performed to obtain acid leaching residue and lithium-rich acid leaching solution.

[0018] Therefore, the overhaul slag and waste slag are mixed and treated in a certain proportion. During the water leaching process of S2, the aluminum and fluorine in the aluminum electrolytic solid waste can enter the solution, and the lithium-containing substances such as lithium fluoride embedded in the aluminum electrolytic solid waste can be exposed and dissociated; subsequently, through simple acid leaching, the lithium can be dissolved and enriched in the acid leaching solution, and the acid leaching solution can be used to prepare lithium salt products through conventional impurity removal and lithium precipitation, so as to realize resource utilization. The whole process is simple and efficient, with stronger applicability to raw materials, and no alkali is needed to dissolve the aluminum and fluorine in the aluminum electrolytic solid waste, which saves more reagents and lowers the cost. At the same time, the recovery and enrichment of lithium in low-lithium materials such as overhaul slag is also realized.

[0019] Furthermore, in S1, the particle size of the aluminum electrolysis solid waste powder is 200-300 mesh.

[0020] Furthermore, in S1, the aluminum electrolysis solid waste powder includes waste refractory materials, waste cathodes and waste slag, and the mass ratio of the waste refractory materials, waste cathodes and waste slag is 5:1-3:1-4.

[0021] Furthermore, in the waste refractory material, the CaF2 content is 5-14wt%, and the NaF content is 0.5-10%; further, in the waste refractory material, the C content is 0.75-10%, the Li content is 0.45-1.5%, the Al2O3 content is 30-50wt%, and the SiO2 content is 25-45wt%.

[0022] Furthermore, the NaF content in the waste cathode is 10-20%; the C content in the waste cathode is 40-60%, the Li content is 0.45-1.2%, and the cryolite content is 0.5-5%.

[0023] Furthermore, in the waste carbon slag, the C content is 15-40%, the Li content is 1-1.5%, the cryolite content is 20-45%, and generally, the NaF content is close to zero.

[0024] Further, in the waste aluminum electrolyte, the C content is 0.1-2%, the cryolite content is 40-75%, the Li content is 1-2%, and generally, the NaF content is close to 0. Further, in S2, the mixing time is 0.5-1h, and the reaction time is 2-4h.

[0025] Optionally, in S2, a plate and frame filter press or a belt filter is used for solid-liquid separation. Preferably, a belt filter is used which has a higher separation efficiency and can wash the wet material online.

[0026] Optionally, in S2, the leached residue is washed with water, and optionally, the amount of washing water is 0.5-1.5 times the dry weight of the leached residue.

[0027] Furthermore, in S3, acid leaching is performed at 80-95° C.; preferably, during acid leaching, the initial liquid-solid mass ratio is controlled to be 3-5:1, preferably 3.5-4.5:1; preferably, the acid leaching time is 2-4h, preferably 2.5-3.5h.

[0028] Optionally, in S3, a plate and frame filter press or a belt filter is used for solid-liquid separation. Preferably, a filter press with a pressing function and a plate and frame filter press with a lower filter residue moisture content are used, which can further reduce the lithium element entrained in the leached residue and improve the lithium recovery rate.

[0029] Furthermore, the acid used for acid leaching is hydrochloric acid and / or sulfuric acid, more preferably concentrated sulfuric acid with a concentration of 93-98wt%, and the amount of concentrated sulfuric acid added is 20-50wt% of the dry weight of the leached residue.

[0030] Further, after S3, the acid leaching residue is slurried to form a slurry with a liquid-solid mass ratio of 3-4:1; a foaming agent, an inhibitor and a collector are added to the slurry, and flotation is performed to obtain a flotation top flow; and then the flotation top flow is solid-liquid separated to obtain a filtrate and carbon;

[0031] Among them, the added amount of the foaming agent is 0.9-1.1wt% of the dry weight of the acid leaching residue; the added amount of the inhibitor is 0.04-0.06wt% of the dry weight of the acid leaching residue; the added amount of the collector is 0.8-1.2wt% of the dry weight of the acid leaching residue, and the collector is composed of gasoline and kerosene in a mass ratio of 65-85:15-35.

[0032] Through chemical leaching, the embedded structure of aluminum electrolytic solid waste is destroyed, and the carbon in the raw materials can be released or dissociated from the structure. In addition, the density of carbon is low, so it is expected to be effectively separated by flotation.

[0033] Through in-depth research, the applicant found that by using gasoline and kerosene in the above proportion to form a composite collector and controlling the addition amounts of foaming agent, inhibitor and collector, good flotation separation of carbon in acid leaching residue can be achieved, while obtaining high carbon recovery rate and carbon grade.

[0034] Optionally, when performing solid-liquid separation on the flotation top flow, a plate and frame filter press or a belt filter is used. Preferably, a belt filter with higher separation efficiency and capable of online washing of wet materials is used.

[0035] Furthermore, the foaming agent is pine oil; the inhibitor is water glass, and the modulus of the water glass is 2.4-2.6.

[0036] Furthermore, after S3, the lithium-rich acid leaching solution is impurity-removed, a water-soluble carbonate is added, lithium is precipitated, the solid and liquid are separated, and the solution is dried to obtain a lithium carbonate product.

[0037] Optionally, when removing impurities from the lithium-rich acid leaching solution, calcium hydroxide or calcium oxide is added to the acid leaching solution to convert fluoride ions, aluminum ions and iron ions into precipitates, followed by solid-liquid separation; then, an appropriate amount of sodium carbonate and sodium hydroxide is added to remove calcium ions and magnesium ions in the filtrate; and then, deep impurity removal is performed by ion exchange, and the calcium and magnesium ions in the solution are selectively adsorbed by the chelating groups on the ion exchange resin, thereby further reducing the content of calcium ions and magnesium ions in the filtrate.

[0038] Optionally, after impurity removal and before lithium precipitation, the acid leaching solution is evaporated and concentrated. Optionally, the concentration of lithium sulfate, sodium sulfate and potassium sulfate in the concentrated solution obtained after evaporation and concentration is 350-380 g / L.

[0039] Optionally, the water-soluble carbonate is sodium carbonate. Optionally, the lithium precipitation reaction temperature is 90-95° C.; Optionally, the lithium precipitation reaction time is 4-6 hours.

[0040] Optionally, the water content of the lithium carbonate product is ≤0.2wt%.

[0041] Optionally, after lithium precipitation, the residual liquid obtained by solid-liquid separation is neutralized to remove excess carbonate, and then evaporated and crystallized to recover sulfate (such as sodium sulfate).

[0042] Furthermore, after S2, acid is added to the leachate at 40-60°C to react until the pH value of the leachate is constant at 8.8-9.2, and the solid-liquid separation is performed to obtain a cryolite product. Thus, cryolite can be recovered by simple acid adjustment, further improving the processing efficiency. Subsequently, the remaining leachate can be subjected to treatments such as cyanide removal and impurity removal, and then evaporated and crystallized to recover sulfates, chlorides and other substances.

[0043] Compared with the prior art, the present invention has the following beneficial effects:

[0044] (1) The treatment method of the present invention can simultaneously realize the coordinated treatment of various aluminum electrolysis solid wastes such as aluminum electrolysis waste refractory materials, waste cathodes, waste slag, etc., and helps to save the amount of reagents used, which is more green and environmentally friendly.

[0045] (2) The treatment method of the present invention can realize the full quantitative recovery of carbon, lithium, cryolite and other substances in aluminum electrolysis solid waste, with good economic benefits.

[0046] (3) The recovery rate of valuable elements of the present invention is high, the purity of the obtained product is high, and it has a high selling value. DETAILED DESCRIPTION

[0047] The present invention will be described in detail below in conjunction with the embodiments. It should be noted that, in the absence of conflict, the embodiments and features in the embodiments of the present invention can be combined with each other. Unless otherwise specified, the relevant percentages refer to mass percentages.

[0048] Example 1

[0049] In this embodiment, the method for processing aluminum electrolysis solid waste to produce battery-grade lithium carbonate and recover carbon and cryolite comprises the following steps:

[0050] (1) Raw material grinding and mixing

[0051] The aluminum electrolysis waste refractory materials, waste cathodes, waste carbon slag and waste electrolytes are crushed and ground to obtain various types of powders with a mesh size of 250.

[0052] The four kinds of ground raw materials are mixed by a double-shaft mixer using a spiral metering scale for measurement. The mass ratio of waste refractory materials, waste cathodes, waste carbon slag and waste electrolytes is 5:2:2:1, and aluminum electrolysis solid waste powder is obtained.

[0053] The waste refractory material contains 10.17% C, 1.37% Li, 4.5% NaF, 40.3% Al2O3, 38.6% SiO2 and 8.14% CaF2.

[0054] The waste cathode contains 55% C, 1.13% Li, 3.72% CaF2 and 19.2% NaF.

[0055] The waste carbon slag contains 20% C, 1.2% Li and 44.85% cryolite.

[0056] The waste aluminum electrolyte contains 0.2% C, 1.47% Li and 71.56% cryolite.

[0057] (2) Water immersion, acid immersion

[0058] The aluminum electrolysis solid waste powder is mixed with water at a liquid-to-solid mass ratio of 4:1, slurried at 85°C for 1 hour, leached for 3 hours, and then filtered through a belt filter to obtain leached residue and leached liquid. The leached residue is washed with 1 times the amount of industrial water and set aside.

[0059] The leaching residue was leached with concentrated sulfuric acid of 98%, the reaction temperature was controlled to be 80°C, the initial liquid-solid mass ratio was 3:1, the slurrying time was 1h, the leaching reaction time was 3h, the amount of concentrated sulfuric acid added was 40% of the dry weight of the leaching residue, and after the reaction, it was filtered through a plate and frame filter to obtain filter residue and acid leaching solution. The filter residue was washed with industrial water of 1 times the amount of the residue to obtain acid leaching residue for standby use.

[0060] (3) Flotation

[0061] The acid leaching residue is slurried, the liquid-solid mass ratio of the slurry is 3:1, the slurrying time is 0.5h, pine oil is used as a foaming agent, and the addition amount is 1% of the acid leaching residue (dry basis); water glass is used as an inhibitor, and the addition amount is 0.05% of the acid leaching residue (dry basis), and the water glass modulus is 2.5; a composite collector of gasoline and diesel is used, the gasoline content in the composite collector is 70%, and the kerosene content is 30%, and the addition amount is 1% of the acid leaching residue (dry basis).

[0062] (4) Acid leaching liquid purification and concentration

[0063] After the acid leaching liquid is subjected to primary impurity removal with calcium hydroxide slurry, solid-liquid separation is performed. Specifically, the temperature is controlled to be 60°C, the liquid-solid mass ratio of the calcium hydroxide slurry is 3:1, the reaction time is 3h, the reaction end point pH is controlled to be 8, the amount of water for washing the primary impurity removal slag is 2 times the amount of slag (dry basis), and the washing liquid is returned to the acid leaching process.

[0064] Subsequently, the acid leaching liquid is subjected to secondary impurity removal using a mixed slurry of sodium carbonate and sodium hydroxide, and then solid-liquid separation is performed. Specifically, the temperature is controlled to be 85°C, the mass ratio of sodium carbonate to sodium hydroxide in the mixed slurry is 5:1, the liquid-solid mass ratio of the solvent to the solute in the mixed slurry is 3:1, the reaction time is 3h, the reaction endpoint pH is controlled to be 12, the amount of water for washing the secondary impurity removal slag is twice the amount of slag (dry basis), and the washing liquid should be returned to the acid leaching process.

[0065] Then, the acid leaching solution was deeply impurized by using an ion exchange resin (resin model CH-93, a product of Lanxiao Company) to make the total concentration of calcium and magnesium ions in the acid leaching solution ≤5ppm.

[0066] The acid leaching solution is evaporated and concentrated using an MVR complete set of equipment, so that after evaporation and concentration, the lithium ion concentration in the concentrated solution is 15 g / L, and the sum of the concentrations of lithium sulfate, sodium sulfate and potassium sulfate is 365 g / L.

[0067] (5) Lithium deposition

[0068] The sodium carbonate powder was measured by a spiral metering scale, and the sodium carbonate and water were mixed in a mass ratio of 3:1 to obtain a slurry, and the heating temperature of the slurry was maintained at 75°C.

[0069] The lithium precipitation adopts the reverse addition method, the reaction temperature is controlled at 95℃, the time is controlled at 4h, and the feeding speed of the concentrated liquid is controlled at 4m 3 / h, after the reaction, the solid and liquid are separated to obtain crude lithium carbonate and lithium precipitation mother liquor.

[0070] The crude lithium carbonate is subjected to slurry washing, wherein the slurry washing uses pure water, the slurry liquid-solid ratio is preferably controlled at 3:1, and the washing is preferably performed twice.

[0071] The washed crude lithium carbonate is slurried with a liquid-to-solid ratio of 25:1, and the slurry is then pumped to a carbonization tower for carbonization and pyrolysis.

[0072] During carbonization and pyrolysis, the CO2 gas supplement amount is controlled at 0.2t / t lithium carbonate, the CO2 gas flow rate is preferably controlled at 4L / min, the pressure in the carbonization tower is controlled at 0.15MPa, the carbonization temperature is controlled at 25°C, the carbonization slurry liquid-to-solid ratio is controlled at 25:1, the pyrolysis temperature is preferably controlled at 95°C, the pyrolysis mother liquor is recycled, and 1 / 5 of the liquid is opened each time to return to configure the sodium carbonate slurry.

[0073] The lithium carbonate is dried in an electric kiln, the drying temperature is controlled at 500°C, and the moisture content of the lithium carbonate product after drying is controlled to be ≤0.2% to obtain a lithium carbonate product.

[0074] (6) Recovery of lithium precipitation mother liquor

[0075] The lithium precipitation mother liquor is decarbonized by adding sulfuric acid dropwise, and the pH value at the reaction end point is controlled to be 7 to obtain the decarbonized mother liquor.

[0076] Then, the decarbonization mother liquor is evaporated and crystallized using an MVR complete set of equipment. 40% of the solution volume is evaporated and the evaporation concentration multiple is 3.25 times to obtain sodium sulfate. After drying, anhydrous sodium sulfate products that can be sold can be obtained. (7) Cryolite Recovery

[0077] Sulfuric acid was added to the leaching solution to precipitate cryolite, the temperature was controlled at 50°C, the final pH was controlled at 9, and the reaction time was 2.5 hours. After the reaction, the solid and liquid were separated, washed, and dried to obtain cryolite products.

[0078] After testing, the obtained lithium carbonate product meets the requirements of the "Battery Grade Lithium Carbonate" (YS / T582-2023) standard Li2CO3-D1 for battery-grade lithium carbonate, and the comprehensive lithium recovery rate (calculated based on the lithium obtained in the lithium carbonate product) reaches 76.47%; the total recovery rate of cryolite reaches 75%; the total recovery rate of carbon reaches 85% (grade reaches 90%), with significant economic benefits.

[0079] Comparative Example 1

[0080] Example 1 was repeated, except that in step (1), the mass ratio of the waste refractory material, the waste cathode, the waste carbon slag and the waste electrolyte was 5:2:2:3.

[0081] After testing, the comprehensive recovery rate of lithium was 58%; the total recovery rate of cryolite was 53%. The possible reasons are that the relative content of waste refractory materials and waste cathodes decreased, the lithium-containing substances in waste carbon slag and waste electrolytes were not dissociated and exposed thoroughly, and part of the lithium elements and cryolite entered the leaching slag and could not be recovered, resulting in a decrease in the comprehensive recovery rate of lithium and cryolite.

[0082] Example 2

[0083] Example 1 was repeated, except that in step (1), the mass ratio of the waste refractory material, the waste cathode, the waste carbon slag and the waste electrolyte was 5:2:2:2.

[0084] After testing, the comprehensive recovery rate of lithium was 68%; the total recovery rate of cryolite was 61%.

[0085] Comparative Example 2

[0086] Example 1 was repeated, except that the collector was gasoline.

[0087] According to the test, the recovery rate of carbon is 75% and the carbon grade is 95%.

[0088] Comparative Example 3

[0089] Example 1 was repeated, except that the collector was kerosene.

[0090] According to the test, the recovery rate of carbon was 90% and the carbon grade was 66%.

[0091] Comparative Example 4

[0092] Example 1 was repeated, except that the gasoline content in the composite collector was 60% and the kerosene content was 40%.

[0093] According to the test, the recovery rate of carbon was 88% and the carbon grade was 80%.

[0094] Example 3

[0095] Example 1 was repeated, except that the gasoline content in the composite collector was 65% and the kerosene content was 35%.

[0096] After testing, the carbon recovery rate was 86% and the carbon grade was 86%.

[0097] Example 4

[0098] Example 1 was repeated, except that the gasoline content in the composite collector was 80% and the kerosene content was 20%.

[0099] According to the test, the recovery rate of carbon was 80% and the carbon grade was 92%.

[0100] Example 5

[0101] Example 1 was repeated, except that the gasoline content in the composite collector was 85% and the kerosene content was 15%.

[0102] According to the test, the recovery rate of carbon was 78% and the carbon grade was 93%.

[0103] Comparative Example 5

[0104] Example 1 was repeated, except that the gasoline content in the composite collector was 90% and the kerosene content was 10%.

[0105] According to the test, the recovery rate of carbon was 76% and the carbon grade was 94%.

[0106] Example 6

[0107] Example 1 was repeated, except that the amount of the composite collector added was 0.8% of the amount of the acid leaching residue (dry basis).

[0108] The recovery rate of carbon was found to be 85%.

[0109] Example 7

[0110] Example 1 was repeated, except that the amount of the composite collector added was 0.9% of the amount of the acid leaching residue (dry basis).

[0111] The recovery rate of carbon was found to be 88%.

[0112] Example 8

[0113] Example 1 was repeated, except that the amount of the composite collector added was 1.1% of the amount of the acid leaching residue (dry basis).

[0114] The recovery rate of carbon was found to be 90%.

[0115] Example 9

[0116] Example 1 was repeated, except that the amount of the composite collector added was 1.2% of the amount of the acid leaching residue (dry basis).

[0117] The recovery rate of carbon was found to be 90%.

[0118] The contents explained in the above embodiments should be understood as these embodiments are only used to more clearly illustrate the present invention, and are not used to limit the scope of the present invention. After reading the present invention, various equivalent forms of modifications to the present invention by those skilled in the art all fall within the scope defined by the claims attached to this application.

Claims

1. A method for treating aluminum electrolysis solid waste, characterized in that: The steps include: S1. Provide aluminum electrolysis solid waste powder; The aluminum electrolysis solid waste powder includes overhaul slag and waste slag, the overhaul slag includes one or more of waste refractory materials and waste cathodes, the waste slag includes one or two of waste carbon slag and waste aluminum electrolyte, and the mass ratio of the overhaul slag to the waste slag is 6-8:1-4; S2, mixing the aluminum electrolyte solid waste powder and water in a solid-liquid mass ratio of 1:3-5, reacting at 80-95° C., separating the solid and the liquid to obtain leaching residue and leaching liquid; S3, after acid leaching the leached residue, solid-liquid separation is performed to obtain acid leaching residue and lithium-rich acid leaching solution.

2. The method for treating aluminum electrolysis solid waste according to claim 1, characterized in that: In S1, the particle size of the aluminum electrolysis solid waste powder is 200-300 mesh.

3. The method for treating aluminum electrolysis solid waste according to claim 1, characterized in that: In S1, the aluminum electrolysis solid waste powder includes waste refractory materials, waste cathodes and waste slag, and the mass ratio of the waste refractory materials, waste cathodes and waste slag is 5:1-3:1-4.

4. The method for treating aluminum electrolysis solid waste according to claim 1, characterized in that: In S2, the mixing time is 0.5-1 h and the reaction time is 2-4 h.

5. The method for treating aluminum electrolysis solid waste according to any one of claims 1 to 3, characterized in that: In S3, acid leaching is performed at 80-95° C.; preferably, during acid leaching, the initial liquid-to-solid mass ratio is controlled to be 3-5:1; preferably, the acid leaching time is 2-4 hours.

6. The method for treating aluminum electrolysis solid waste according to claim 5, characterized in that: The acid used for acid leaching is hydrochloric acid and / or sulfuric acid, more preferably concentrated sulfuric acid with a concentration of 93-98wt%, and the amount of concentrated sulfuric acid added is 20-50wt% of the dry weight of the leached residue.

7. The method for treating aluminum electrolysis solid waste according to any one of claims 1 to 3, characterized in that: After S3, the acid leaching residue is slurried to form a slurry with a liquid-to-solid mass ratio of 3-4:1; a foaming agent, an inhibitor and a collector are added to the slurry, and flotation is performed to obtain a flotation top flow; then the flotation top flow is solid-liquid separated to obtain a filtrate and carbon; Among them, the added amount of the foaming agent is 0.9-1.1wt% of the dry weight of the acid leaching residue; the added amount of the inhibitor is 0.04-0.06wt% of the dry weight of the acid leaching residue; the added amount of the collector is 0.8-1.2wt% of the dry weight of the acid leaching residue, and the collector is composed of gasoline and kerosene in a mass ratio of 65-85:15-35.

8. The method for treating aluminum electrolysis solid waste according to claim 7, characterized in that: The foaming agent is pine oil; the inhibitor is water glass, and the modulus of the water glass is 2.4-2.

6.

9. The method for treating aluminum electrolysis solid waste according to any one of claims 1 to 3, characterized in that: After S3, the lithium-rich acid leaching solution is impurity-removed, a water-soluble carbonate is added, lithium is precipitated, the solid and liquid are separated, and the solution is dried to obtain a lithium carbonate product.

10. The method for treating aluminum electrolysis solid waste according to any one of claims 1 to 3, characterized in that: After S2, acid is added to the leaching solution at 40-60°C to react until the pH value of the leaching solution is constant at 8.8-9.2, and the solid-liquid is separated to obtain a cryolite product.

Citation Information

Patent Citations

  • Process for preparing kryocide

    CN101376518A

  • Water leaching-flotation method for recovering carbons and electrolytes from waste cathode carbon blocks in aluminum electrolysis cell

    CN105926007A

  • Method for comprehensively recovering aluminum electrolysis waste cathode carbon blocks through ultrasonic-assisted floatation and pressure acid leaching

    CN106077037A

  • Cooperative treatment and resource utilization method for aluminum electrolysis overhaul slag and carbon slag

    CN117139352A

  • Method for preparing aluminum fluoride and aluminum oxide by decarburization and sodium removal of aluminum electrolysis carbon residue

    US20220144658A1